The Perfomance of a herd of N'dama and West African Shorthorn cattle in the forest zone of Ghana - Owusu, E.A. (1985)
A comparative study of N'Dama and West African Shorthorn (WASH) herds at Kumasi University farm. Production records of both breeds were analysed. Age at first calving and calving interval between the breeds was not significant. Month of birth and parity significantly affected calving interval. Month of birth significantly affected age at first calving in both breeds.